AB0008 Blys/April Gene Expression in Synovial Fluid and Blood in Rheumatoid Arthritis. (10th June 2014) - Mas, L.A.; Saurit, V.; Colazo, M.; Palomino, E.V.; Caeiro, F.; Alvarellos, T.; Alvarellos, A.
Abstract : Background: The B Lymphocyte Stimulator (BLyS) and A PRoliferation-Inducing Ligand (APRIL) signaling pathway has an important role in the selection, maturation and survival of B cells. Dysregulation of BLyS/APRIL is involved in the pathogenesis of B-cell related autoimmune diseases including Rheumatoid Arthritis (RA). Synovial fluid cells are highly activated in patients with active RA inducing lymphocyte proliferation, expression of cell surface molecules, cytokine and auto antibody secretion. Objectives: The purpose of this work is to evaluate Synovial Fluid (SF) and Peripheral Blood (PB) mRNA expression of BLyS and APRIL in RA patients. Methods: SF and PB were obtained and classified in two groups, Group I: active RA patients with DAS 28 score >5.1 (n=11, 8F/3M, age: 56, 2±20, 9; range: 17-84) and Group II, control: Osteoarthritis (OA, n=20, 13F/7M, age: 69, 8±9, 5, range: 47-84). Levels of BLyS and APRIL expression were evaluated using Quantitative Real Time PCR (QPCR). All amplifications were carried out in duplicate and threshold cycle (Ct ) scores were averaged for calculations of relative expression values. The Ct scores were normalized against Ct scores by subtracting the corresponding β2Microglobuline (β2M) control, or ΔCt=Ct, gene - Ct, B2M . To test for differential gene expression between groups, a two sample t-test was performed to compare the DCt in the two groups. Results: BLyS and APRIL gene expression is shown in Table 1 . ΔCt is inversely proportional to the gene expression level. Analysis of PB showed no significant difference in gene expression between RA and OA. In SF, we observed a significant difference for BLyS and APRIL expression between Group I vs. Group II (p=0, 002 and p=0, 024 respectively). After t test, we evaluated data from Δ Ct analysis observing that in SF, mRNA of BLyS and APRIL in Group I was higher than those from Group II. Conclusions: Gene expression of BLyS/APRIL in PB does not correlate with expression in SF. Increased BLyS and APRIL expression in active RA SF can be linked to B cell activation and maintenance in RA synovium. References: Moura RA, et al. BAFF and TACI gene expression are increased in patients with untreated very early Rheumatoid Arthritis. The journal of Rheumatology 2013. La Cava A. Targeting the BLyS-APRIL signaling pathway in SLE. Clin Immunol 2013. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2971